1985
DOI: 10.1093/infdis/152.6.1192
|View full text |Cite
|
Sign up to set email alerts
|

The Source of Murine Cytomegalovirus in Mice Receiving Kidney Allografts

Abstract: The sources of cytomegalovirus (CMV) infection in kidney transplant recipients include reactivation of latent endogenous virus in the recipient or reactivation of latent virus in donated blood or kidney. In the present study, kidneys from mice latently infected with one strain of murine CMV were transplanted into either uninfected recipients or recipients latently infected with a different strain of murine CMV; the recipients were immunosuppressed, subsequently were cultured for murine CMV, and the infecting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…18,19 However, later, a dominant MCMV resistance trait expressed by C57BL/6 mice used as recipients in these studies was suggested, which therefore limited the scope of these results. Experimental models have suggested that a large proportion of mouse CMV (MCMV) viremia in D+R+ recipients originated from the recipient.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, later, a dominant MCMV resistance trait expressed by C57BL/6 mice used as recipients in these studies was suggested, which therefore limited the scope of these results. Experimental models have suggested that a large proportion of mouse CMV (MCMV) viremia in D+R+ recipients originated from the recipient.…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly argued against T and B lymphocytes, macrophages, and dendritic cells (DCs) being major reservoirs of latent mCMV in the spleen, a conclusion supported by later work of Pomeroy and colleagues (86). Sim-ilarly, Klotman and colleagues (54) as well as Hamilton and Seaworth (44) concluded that in kidney transplantation, donor kidney is the source of latent mCMV and that the latent viral genome is harbored by renal peritubular epithelial cells (53). A first hint for mCMV latency in ECs within the liver was provided by in situ PCR images presented by Koffron and colleagues (59) showing nuclear staining in cells with a microanatomical localization suspicious of liver sinusoidal ECs (LSECs).…”
mentioning
confidence: 99%
“…Latent infection has been demonstrated in the spleen (15,28,38,39), kidney (14,18), salivary gland (6,48), and lung (3). In addition, human hematopoietic cells, including bone marrow cells, have been found to contain latent HCMV (12,30).…”
mentioning
confidence: 99%